Teachers’ Strategies for Developing Students’ Religious Character through Aswaja Activities - Muhammad Taufiq Hidayat; Ida Lathifatul Umroh; Winnuly (Journal of Educational Management Research, 2026)
This study aims to explore teachers’ strategies for strengthening students’ religious character through Aswaja activities and to examine the supporting and inhibiting factors as well as the impacts of these activities on students’ character development. This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, participant observation, and documentation involving school leaders, teachers, and students selected through criterion-based purposive sampling. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion verification. The findings revealed that teachers strengthened students’ religious character through integrated strategies involving systematic planning, religious habituation, teacher modelling, and leadership-oriented learning. The implementation of Aswaja activities was supported by institutional commitment, teacher collaboration, and a strong religious school culture, although several challenges emerged related to students’ motivation, preparedness, and technical limitations. Furthermore, Aswaja activities contributed to improving students’ religious discipline, responsibility, leadership, self-confidence, communication skills, and social awareness. This study implies that Aswaja-based character education can serve as an effective approach for integrating religious values with students’ personal and social competency development in vocational education contexts.